Structure and properties of multilayer coatings based on CoCrAlY/Al2O3 obtained by detonation spraying - Rakhadilov, B; Tyurin, Yu.N.; Kolisnichenko, O.V.; Kakimzhanov, D.N.; Zhurerova, L.G. (Eurasian Journal of Physics and Functional Materials, 2026)
Ceramic coatings are used to protect against high-temperature oxidation of metal products. The efficiency of the technology of detonation spraying of two-layer coatings of aluminum oxide ( Al2O3 ) and a heat-resistant alloy (CoCrAlY) on the surface of a sample made of steel 12X18H10T was studied. A multi-chamber detonation unit was used in the work, providing high speed (up to 1000 m/s) and a 60– 80% utilization rate of the sprayed material. We used an oxygen-neutral combustible mixture based on propane-butane. The coating material has a smooth gradient of properties from ceramic to sample substrate The complex of the obtained structural and physical-mechanical properties of the coating material makes it possible to predict its high performance under conditions of high-temperature oxidation. © 2022, Eurasian Journal of Physics and Functional Materials. All Rights Reserved.Recommended CitationRakhadilov, B. K.; Tyurin, Yu. N.; Kolisnichenko, O. V.; Kakimzhanov, D. N.; and Zhurerova, L. G. (2022) "Structure and properties of multilayer coatings based on CoCrAlY/Al2O3 obtained by detonation spraying," Eurasian Journal of Physics and Functional Materials: Vol. 6: No. 3, Article 8.DOI: https://doi.org/10.32523/ejpfm.2022060308